The Sauvé-Kapandji Procedure - Lluch, Alberto (Journal of Wrist Surgery, 2013)
Arthrodesis is the most reliable and durable surgical procedure for the treatment of a joint disorder, and its only disadvantage is the loss of motion of the fused joint. The distal radioulnar joint can be arthrodesed, while forearm pronation and supination are maintained or even improved by creating a pseudoarthrosis of the ulna just proximal to the arthrodesis. This is known as the Sauvé-Kapandji (S-K) procedure. The Sauvé-Kapandji differs from the Darrach procedure in that it preserves ulnar support of the wrist, as the distal radioulnar ligaments and ulnocarpal ligaments are maintained. Aesthetic appearance is also superior after the S-K procedure, as the normal prominence of the ulnar head, most noticeable when the forearm is in pronation, is maintained. However, the S-K is not free of possible complications, such as nonunion or delayed union of the arthrodesis, fibrous or osseous union at the pseudoarthrosis, and painful instability at the proximal ulna stump. All of these complications can be prevented if a careful surgical technique is used.
Keywords: arthrodesis; distal radioulnar joint; ulnocarpal impaction; triangular fibrocartilage